The biology and systematics of South African pipefishes of the genus Syngnathus - Mwale, Monica (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2007)
Syngnathus the most speciose genus in the family Syngnathidae is widely in the Atlantic and Eastern Pacific oceans. However, it is poorly represented in the Indian Ocean with the only two species, Syngnathus temminckii and S. watermeyeri occurring in Southern African estuaries and coastal areas. Syngnathus temminckii the most common South African pipefish has been synonymised with S. acus, as the morphological and genetic divergence between these two populations has not been documented. There is also uncertainty in the taxonomic status of S. watermeyeri, an endemic estuarine pipefish that is restricted to two Eastern Cape estuaries. The purpose of this study was therefore to compare biological, morphological and genetic variation of South African Syngnathus species among different populations/locations, and with European populations of S. acus. Sixteen meristic and ten morphometric characteristics were quantified from specimens obtained from field as well as various international natural history museum collections. Univariate (ANOVA) and multivariate (principal component analysis and discriminant analyses) analyses were used to assess morphological differences among the species. Morphometric variables were adjusted as ratios of the standard length and using an allometric procedure. ANCOVA analysis indicated significant differences between S. acus and S. temminckii for the relationships of the standard length (SL) and all morphological characters. There was no significant correlation between SL and snout length, snout depth, inter-orbital width and trunk depth for S. watermeyeri. The analyses provided evidence for distinct populations of S. acus, S. temminckii and S. watermeyeri although morphological character differentiation was greater between S. watermeyeri and the other two larger species. Although, significant differences were observed for meristic characters, pairwise comparisons did not reflect a clear pattern of variability. Most of the measured morphological characters contributed more than 70% to the morphological variation between the populations. Plot of the canonical scores for the variables resulted in the specimens clustering according to species groups and locations of S. temminckii. Sequences of 750 base pairs of the mitochondrial cytochrome gene from 11 localities were compared with published sequences of other species of Syngnathus. Phylogenetic analysis was performed using parsimony, maximum likelihood (ML) and Bayesian inference (BI). The South African species were revealed to be sister-taxa with about 6 % divergence, while S. temminckii and S. acus had about 11% sequence divergence. 20 haplotypes among 46 total specimens from the three species. Gene flow was estimated at approximately 3 migrants per generation between the two South African populations and about 1 per generation between S. temminckii and S. acus. Such strong stock structuring among presumably recently established post-Pliocene (< 2 Million years ago) populations suggests that these species are reproductively isolated. Morphological and genetic variation observed in this study combined with current knowledge of life history attributes of the South African pipefishes indicate that conservative management decisions are necessary until the patterns and extent of differentiation among populations species-wide can be investigated further. It is thus being proposed that the name of the South African population of S. acus be changed to Syngnathus temminckii (Kaup, 1856).
Keywords: Pipefishes -- South Africa; Syngnathus -- South Africa